Permit Markets, Carbon Prices and the Creation of Innovation Clusters - Hans Gersbach; Marie-Catherine Riekhof (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Innovation clusters that combine public basic research and applied research performed by private firms may be needed for greater technological advances to slow down climate change. We use a multi-country model with emissions permit trade to examine how international climate policy can induce countries to create such clusters. We allow for a varying degree of cooperation between the countries, represented by different carbon price targets. We find that a minimal carbon price is needed to attract applied research firms, but countries may nevertheless fail to invest in basic research. We construct a mechanism that can overcome this barrier and that can induce the first-best creation of innovation clusters. The mechanism involves a combination of few permits given to the country with the lowest costs for basic research, fair burden-sharing and maximal grandfathering.
Keywords: H23; Q54; O32; 330; International permit markets; Carbon prices; Innovation clusters; Basic research; Applied R&D; Climate change mitigation; Externalities